Analysis and Review of the Newspapers Neday-e Iran and Neday-e Irani, the First Successful Experience of Women Journalism in Shiraz - ziba ghafory (زن در فرهنگ و هنر)
In the constitutional era, Iranian women graduallyincreasingly entered the media. First, the women of the capital city entered this arena, and shortly thereafter, the women of the cities also entered. They quickly achieved success in this field, publishing significant publications and engaging in significant activities. The objective of this investigation is to determine the manner in which the “Neday-e Iran” and “Neday-e Irani” periodicals analyzed political and social matters in Iran during the years 1947 to 1952.The political and social issues of the 1940s and 1950s have been critically examined by the newspapers Neday-e Iran and Neday-e Irani, which were published in Shiraz by Mrs. Nusrat Al-Mouluk Kashmirizadeh, have taken a critical look at the political and social issues of their time.In the field of political affairs, these newspapers published sharp articles and analyses that criticized the performance of the statesmen and firmly opposed the underperforming and xenophobic statesmen. Conversely, these newspapers also monitored and mirrored the social issues and challenges of Shiraz city. They sought to resolve these issues by imposing demands on the administrators and officials of Shiraz. These two newspapers also addressed issues concerning women, emphasizing the necessity of societal change and transformation to enhance the status of women.  Archival, library, and field methods (interviews) are employed to gather information in the current study. The research methodology is historical and descriptive, with an analytical and analytical approach